Upland rice breeding for drought tolerance (review) - P. I. Kostylev; А. V. Aksenov (Зерновое хозяйство России, 2021)
Upland rice grown by rice farmers is having the lowest productivity in the rice production system. Drought stress is the most severe abiotic constraint for upland rice. The improvement of rice productivity in such ecosystems is essential to meet the food security needs of the population. Therefore, the cultivation of drought tolerant rice is becoming an increasingly important task. Numerous minor traits have been proposed to assist plant breeders in their selection, but most of these traits are not used in breeding because they are not practical for breeding purposes, have low heritability, or are not very correlated with grain productivity. There has been shown, that standardization of drought screening improves heritability under stress to the values similar to those obtained for the yields under well-watered conditions. Nowadays there has now been proven that drought-resistant varieties can be developed by direct selection for productivity under stressful conditions. Currently, there have been identified many quantitative trait loci (QTL) of drought tolerance in rice, but only a few of them are suitable for use in marker breeding. However, the identified genes of great drought tolerance can be effectively used in breeding for drought tolerance. The use of molecular markers will improve the efficiency of breeding work. The current review has briefly considered the importance of rice, its various production systems, and the impact of drought stress on rice production. There have been discussed the physiological mechanisms contributing to the maintenance of grain productivity under drought conditions, and there have been analyzed the breeding methods for improvement of drought resistance.